2011
DOI: 10.2174/138920111798377076
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis: Recent Discoveries and Novel Perioperative Treatment Strategies with Particular Interest in the Hemostatic Compound Desmopressin

Abstract: Metastatic disease is responsible for most of cancer lethality. A main obstacle for therapy of advanced cancers is that the outcome of metastasis depends on a complex interplay between malignant and host cells. The perioperative period represents an underutilized window of opportunity for cancer treatment where tumor-host interactions can be modulated, reducing the risk of local recurrences and distant metastases. Blood-saving agents are attractive compounds to be administered during tumor surgery. Desmopressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 53 publications
1
34
0
1
Order By: Relevance
“…At present, the primary methodology for breast cancer therapy is resective surgery followed by hormonal therapy, chemotherapy, radiotherapy and/or biological therapy (8,9). Although great progress has been made in the earlier diagnosis and systemic therapy of patients with breast cancer in recent years, recurrence or distant metastasis continue to present major barriers to the successful treatment of breast cancer (10,11). Therefore, fully understanding the molecular mechanisms underlying the progression of breast cancer may be critical for the development of effective therapeutic strategies against breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the primary methodology for breast cancer therapy is resective surgery followed by hormonal therapy, chemotherapy, radiotherapy and/or biological therapy (8,9). Although great progress has been made in the earlier diagnosis and systemic therapy of patients with breast cancer in recent years, recurrence or distant metastasis continue to present major barriers to the successful treatment of breast cancer (10,11). Therefore, fully understanding the molecular mechanisms underlying the progression of breast cancer may be critical for the development of effective therapeutic strategies against breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative administration of DDAVP at high doses of 1 μg/kg prolonged disease-free and overall survival. An extended trial recently confirmed these results, showing a reduced incidence of local relapses and lung metastasis in treated animals and a particular survival benefit in cases with more aggressive carcinoma (6). It is likely that DDAVP infusion not only inhibits perioperative metastastic events but also combats micrometastases that occurred before surgery.…”
mentioning
confidence: 86%
“…However, we agree with Dr Alonso's proposal that raising the levels of VWF within the blood vessels at the premetastatic sites by a pharmacological intervention using desmopressin (DDAVP) may be another strategy. Compared with the development and clinical trials of ADAM28-selective inhibitors, the treatment using DDAVP may have several advantages: First, DDAVP has been clinically used without adverse effects for patients with von Willebrand disease or hemophilia A, and thus it appears to be a very safe drug (5,6). Second, antimetastatic effects of DDAVP have been demonstrated in the experimental animal models by Dr Alonso's group (6).…”
Section: Correspondence Responsementioning
confidence: 99%
“…In this regard, an approach could raise the levels of vWF by a pharmacological intervention. We previously reported that intravenous administration of desmopressin (dDAVP), a synthetic peptide analogue of vasopressin, can inhibit the formation of metastasis in the experimental models of breast and colon cancer at clinically relevant doses [5]. The compound induces an abrupt release of vWF from endothelial cells through a specific agonistic action on V2 vasopressin receptors, with resulting haemostatic and antitumor effects.…”
mentioning
confidence: 99%
“…The compound induces an abrupt release of vWF from endothelial cells through a specific agonistic action on V2 vasopressin receptors, with resulting haemostatic and antitumor effects. The perioperative and early postoperative period is an attractive window of opportunity to take advantage from this knowledge, aiming to combat the metastatic disease [5]. Since the release of vWF may favour the collapse of incipient metastatic foci, further evaluation of the dDAVP as well as other vasopressin analogues in clinical trials is warranted.…”
mentioning
confidence: 99%